Formation of a sequence chains of nanosecond ion bunches for injection in a linear accelerator - Butenko, V.I.; Yegorov, A.M.; Ivanov, B.I.; Prishchepov, V.P.; Shulika, N.G. (Вопросы атомной науки и техники, 2014)
Currently there are generators of intense ion beams of nanosecond duration. For the purpose of the injection such ions into a linear accelerator the formation of a sequence ~10² ion bunches of a duration of 20 ns, a current of ~100 mA total current pulse duration of about 1 μs is considered in this work. In this case, bunches of highly charged ions (HCI) of aluminum are generated by field emission by applying a voltage of 400 kV, a duration of 50 ns at a block of aluminum emitters, spaced along the axis of the injector. The injector consists of a sequence co-axial emitters, a grounded accelerating grid and a retarding-and-turning grid. Trough the retarding-and-turning grid a current is passed from the current pulse generator, which creates an azimuthal magnetic field directing HTI along the axis. The analytical calculations that determine the parameters and confirming the possibility of the technical realization of such a device are shown. В настоящее время имеются генераторы интенсивных ионных пучков наносекундной длительности. С целью инжекции таких ионов в линейный ускоритель в данной работе рассмотрено формирование последовательности ~10² ионных сгустков длительностью 20 нс, током ~100 мА в суммарный токовый импульс длительностью ~1 мкс. При этом сгустки высокозарядных ионов алюминия (ВЗИ) генерируются автоэмиссион-ным путем при подаче напряжения 400 кВ, длительностью 50 нс на блок острийных эмиттеров из алюминия, разнесенных в пространстве вдоль оси инжектора. Инжектор состоит из коаксиально расположенных эмиттеров, заземленной ускоряющей сетки и замедляюще-оворотной сетки. Через замедляюще-поворотную сетку пропускается ток от генератора импульсного тока, создающий азимутальное магнитное поле, направляющее ВЗИ вдоль оси. Приведены аналитические расчеты, определяющие параметры и подтверждающие возможность технической реализации подобного устройства. Наразі є генератори інтенсивних іонних пучків наносекундної тривалості. З метою інжекції таких іонів у лінійний прискорювач у цій роботі розглянуто формування послідовності ~10² іонних згустків тривалістю 20 нс, струмом ~100 мА в сумарний струмовий імпульс тривалістю ~1 мкс. Згустки високозарядних іонів алюмінію (ВЗІ) генеруються автоемісійним шляхом при подачі напруги 400 кВ, тривалістю 50 нс на блок вістрійних емітерів з алюмінію, рознесених у просторі уздовж осі інжектора. Інжектор складається з коаксіально розташованих емітерів, заземленої прискорюючої сітки і сповільнюючо-поворотної сітки. Через сповільнюючо-поворотну сітку пропускається струм від генератора імпульсного струму, що створює азимутальне магнітне поле, яке спрямовує ВЗІ уздовж осі. Наведені аналітичні розрахунки, що визначають параметри й підтверджують можливість технічної реалізації подібного пристрою.